Study of Poly(amidoamine) Based Dendrimers as Adsorbents for Heavy Metals Removal Through Bibliometric Analysis - Kanak Saxena (Indonesian Society of Limnology, 2024)
Heavy metals have presented various threats to human health and the environment. Consequently, the removal of heavy metals has remained a primary focus for researchers to safeguard water quality. Among the array of available techniques, the adsorption method utilizing dendrimers has garnered the attention of researchers due to its ease of application and impressive results in the removal of heavy metals. Poly(amidoamine) (PAMAM) based dendrimers have been employed in this domain using adsorption techniques since 1999. This manuscript presents a comprehensive bibliometric analysis, coupled with visualization mapping using VOSviewer software, covering research in this field up to the year 2022. The analysis encompasses trends in paper publications across journals, countries, as well as citation and co-citation patterns among authors and countries. A total of 96 articles were shortlisted based on a defined selection criterion. The majority of articles were published between 2019 and 2022, with 2019 standing out as the peak year for publications. The total published articles garnered a total citation count of 4490, with the most cited article in the list receiving a total of 270 citations. A total of 61 journals are associated with the published articles, with the